Desintermediação financeira: o papel da securitização como mecanismo de financiamento para empresas - Santos, Cláudio Gonçalves dos (2013)
The market for financial disintermediation, through financial asset securitization in Brazil has been growing in recent years. Constant improvements in regulation, has contributed to closer business investors in a regulated environment, making it possible to carry out financial transactions outside the traditional banking financial market. There is much yet to be done by regulators to strengthen the market. This work seeks to contribute to the theme, suggesting some changes in the regulations. From 2000 to 2012, the securitization transactions through structures with CRI, FIDC, and FII moved R$ 149.8 billion, equivalent to 3.4% of the GDP in 2012. Operations tend to increase, however, there are some variables in the Brazilian market, which will be analyzed in this work, that need to be adjusted so that the securitization market is nimble robustly contributing to the financing of companies. In this paper we analyze the main sources of funding for companies, as equity and the various sources of debt, and securitization. Will also analyzed the market for corporate debt, without which the operations are limited to the traditional banking system. The development of the debt Market strengthens the growth of the securitization market